American Literature in the World: An Anthology from Anne Bradstreet to Octavia Butler, edited by Wai Chee Dimock et al.: (A Book Review) - Iuliano, Fiorenzo (Review of International American Studies, 2019)
A book review of: Wai Chee Dimock, et. al., editors, American Literature in the World: An Anthology from Anne Bradstreet to Octavia Butler. Columbia UP, 2017.